Waste Analysis in The Production Process Urea Fertilizer Using The Lean Six Sigma Method and Recommendations for Improving Failure Mode Effect Analysis (FMEA) at PT. Damai Sejahtera - Tivani Nava Arier; Rochmoeljati Rochmoeljati; Isna Nugraha (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
Agriculture plays an important role in the Indonesian economy, fertilizer is an important element in the development of the agricultural sector, especially urea fertilizer. PT. Damai Sejahtera, as one of the largest fertilizer producers in Indonesia, experienced waste in the urea fertilizer production process. In this study, lean six sigma was utilized. Using a lean approach, a reduction in non-value-added activities formed by the nine types of waste of 1360 to 1276 or 6.17% was achieved. However, using six sigma, it was found that the production process was not satisfactory as it resulted in many product defects with 36,331 DPMO and a sigma level of 3.32. Improvement suggestions to increase the sigma value were obtained through FMEA. Through this research, Process Cycle Efficiency was obtained from 74.85% to 80.35%.